2022
DOI: 10.3389/fpls.2022.929747
|View full text |Cite
|
Sign up to set email alerts
|

GmFT3a fine-tunes flowering time and improves adaptation of soybean to higher latitudes

Abstract: Onset of flowering of plants is precisely controlled by extensive environmental factors and internal molecular networks, in which FLOWERING LOCUS T (FT) is a key flowering integrator. In soybean, a typical short-day plant, 11 FT homologues are found in its genome, of which several homologues are functionally diversified in flowering pathways and the others including GmFT3a are yet unknown. In the current study, we characterized GmFT3a, which is located on the same chromosome as the flowering promoters GmFT2a a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…FT is regarded as the integrator of signals in the flowering pathway of plants (Andrés & Coupland, 2012). In soybean, FT homologs are divided into two types including floral promoters (e.g., GmFT2a , GmFT2b , GmFT3a , GmFT3b , GmFT5a and GmFT5b ) and floral inhibitors (e.g., GmFT1a and GmFT4 ) (Cai et al, 2020; Kong et al, 2010; Liu et al, 2018; Nan et al, 2014; Su et al, 2022, 2024; Sun et al, 2011; Yuan et al, 2022). To confirm the expression pattern of GmFT homologs during reproductive growth, we performed qPCR targeting GmFT2a , GmFT3a , GmFT3b , GmFT5a and GmFT6 at vegetative growth stages (V1, V2 and V3) and reproductive growth stages (R1, R3 and R5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FT is regarded as the integrator of signals in the flowering pathway of plants (Andrés & Coupland, 2012). In soybean, FT homologs are divided into two types including floral promoters (e.g., GmFT2a , GmFT2b , GmFT3a , GmFT3b , GmFT5a and GmFT5b ) and floral inhibitors (e.g., GmFT1a and GmFT4 ) (Cai et al, 2020; Kong et al, 2010; Liu et al, 2018; Nan et al, 2014; Su et al, 2022, 2024; Sun et al, 2011; Yuan et al, 2022). To confirm the expression pattern of GmFT homologs during reproductive growth, we performed qPCR targeting GmFT2a , GmFT3a , GmFT3b , GmFT5a and GmFT6 at vegetative growth stages (V1, V2 and V3) and reproductive growth stages (R1, R3 and R5).…”
Section: Resultsmentioning
confidence: 99%
“…GmFT2a and GmFT5a, the floral‐promoting FT homologs in soybean, have been demonstrated as the mobile factors that move from leaves to roots (Wang et al, 2021). In soybean, FT homologs serve various roles in flowering: GmFT2a , GmFT2b , GmFT3a , GmFT3b and GmFT5a promote flowering and maturity, while GmFT1a and GmFT4 repress these processes (Cai et al, 2020; Kong et al, 2010; Lee et al, 2021; Liu et al, 2018; Nan et al, 2014; Su et al, 2022; Sun et al, 2011; Yuan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Photoperiod, which refers to the length of the day, is a significant environmental signal that has been extensively investigated for its role in regulating flowering in many plants, such as soybeans and rice [ 19 , 51 , 52 ]. However, in these crops, photoperiod mainly regulates the timing of flowering (the differentiation of the floral buds) and is not directly involved in sex differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In soybean, the functions of GmFT1a , GmFT2a / b , GmFT3a/b , and GmFT5a in regulating flowering and maturity have been studied (Cai et al, 2020; Chen et al, 2020; Liu et al, 2018; Su et al, 2022; Takeshima et al, 2019; Yuan et al, 2022), but the role and mechanism of GmFT5b remained unclear. In this study, we demonstrated that GmFT5b is a conserved positive regulator of floral development in soybeans.…”
Section: Discussionmentioning
confidence: 99%
“…A major GmFT2b enables earlier flowering and adaptation to higher latitudes (Chen et al, 2018). GmFT3a promotes flowering under LD conditions, and the GmFT3a ‐Hap2 haplotype enhances adaptation to high latitudes (Yuan et al, 2022). GmFT1a and GmFT4 are flowering repressors, but research on natural variants' geographic distribution is limited (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%